AN OVERVIEW OF ENGLISH LANGUAGE PROFICIENCY INDEX IN EFL-COUNTRIES - Ni Wayan Satri Adnyani (Yavana Bhasha : Journal of English Language Education, 2022)
The English Proficiency Index (EPI) ranking released by Education First (EF) shows that Indonesian EPI falls under Vietnam in 2016 and commits a decreasing trend since 2011. Besides, other EFL-countries, e.g., Belgium and Argentina, could reach the 11th and 19th world ranking in the same year. These phenomena showed that Indonesian had problems in improving English language proficiency. Therefore, this paper is aimed at; (1) pointing out the factors affecting EPI from social-cultural, legal and educational perspectives, (2) factors affected by EPI, and, (3) recommendations for improving EPI based on the other EFL-countries with high EPI. Keywords: English Language Proficiency Index (EPI), EFL-countries